Case Report: Low-Frequency Repetitive Transcranial Magnetic Stimulation to Dorsolateral Prefrontal Cortex and Auditory Cortex in a Patient With Tinnitus and Depression - Chang, Chun-Hung; Wang, Wen-Lung; Shieh, Yu-Hui; Peng, Han-Yuan; Ho, Chen-Syuan; Tsai, Hsin-Chi (Frontiers in Psychiatry, 2022)
Repetitive transcranial magnetic stimulation (rTMS) has been widely used as a promising therapy for tinnitus. However, the exact target and stimulation sequence of rTMS that is most effective for treating tinnitus remains unclear. Here, we report a case of a 62-year-old man with treatment-refractory tinnitus and depression whose symptoms markedly improved after undergoing low-frequency rTMS over the right-side dorsolateral prefrontal cortex and left auditory cortex area. Our report indicates that low-frequency rTMS treatment that stimulates multiple brain regions sequentially is feasible and may clinically benefit patients with tinnitus and depression.